Access services’ shifts in Azerbaijani academic libraries during COVID-19: the case of ADA University Library - Elchin Chingizoglu Mammadov (15393415) (2023)
This presenation was given by Elchin Chingizoglu Mammadov, Library and Information Services, ADA University, Baku, Azerbaijan  The COVID-19 pandemic made a unsuspected long-term strike to the academic library environment in Azerbaijan as well as elsewhere in the early spring of 2020. In particular, the consumption of physical resources (collections, facilities, etc.) was experienced via campus closures, budget cuts, strict quarantine requirements, enforced social distancing, etc. This article examines the respond of Azerbaijani academic libraries to the COVID-19 pandemic in the case of ADA University Library. The similarities and contrast of actions brought to the fore in against to global experience. The role of online information resources access, exchange, ILL and Electronic Document Delivery during pandemic is specifically investigated. The author describes the prompt transitions of ADA University Library in early spring 2020 due to the shutdown of university campus. Multititle solutions were implemented including online circulation and reference services, preparation of online tutorials, strengthening institutional repository with open access resources and organization of usage, full utilization of electronic ILL and Document Delivery services. Moreover, services like consultation, technical, experience sharing support to partner universities and institutions were organized. The author also outlines the role of long-term strategic view of ADA university leadership, that before Pandemic the library passed through successful digital transformations being ready for uncertainties.